2016
DOI: 10.1073/pnas.1607542113
|View full text |Cite
|
Sign up to set email alerts
|

Civil conflict sensitivity to growing-season drought

Abstract: To date, the research community has failed to reach a consensus on the nature and significance of the relationship between climate variability and armed conflict. We argue that progress has been hampered by insufficient attention paid to the context in which droughts and other climatic extremes may increase the risk of violent mobilization. Addressing this shortcoming, this study presents an actor-oriented analysis of the drought-conflict relationship, focusing specifically on politically relevant ethnic group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
197
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(206 citation statements)
references
References 53 publications
7
197
1
1
Order By: Relevance
“…The degree to which climate or environmental change contributes to social or political unrest or conflict is a hotly debated topic at the present time and one with no established consensus (Bernauer et al 2012, von Uexkull et al 2016. The field of research consists of studies that explore the relationship between climate and armed conflict, relying on both qualitative and quantitative methodological approaches (Bernauer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The degree to which climate or environmental change contributes to social or political unrest or conflict is a hotly debated topic at the present time and one with no established consensus (Bernauer et al 2012, von Uexkull et al 2016. The field of research consists of studies that explore the relationship between climate and armed conflict, relying on both qualitative and quantitative methodological approaches (Bernauer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A study on the nexus of droughts and conflict in Asia and Africa found that droughts increase the likelihood of conflicts for groups which are dependent on agriculture and those who are politically marginalized in countries with high poverty levels (Uexkull et al 2016). People whose livelihoods depend on agriculture will be immediately affected by changes in the natural environment.…”
Section: Povertymentioning
confidence: 99%
“…10 Fjelde and von Uexkull 2012;O'Loughlin et al 2012;Hsiang, Meng, and Cane 2011;Theisen, Holtermann, and Buhaug 2011;Buhaug 2010;Burke et al 2009. 11 CAN 2007 Von Uexkull et al 2016;Caruso, Petrarca, and Ricciuti 2016;Schleussner et al 2016;Buhaug et al 2015;Gartzke and Böhmelt 2015;Smith 2014;Maystadt and Ecker 2014;Koubi et al 2012. 13 See, e.g., Burke, Hsiang, and Miguel 2015a;Kelley et al 2015;Reuveny 2007.…”
mentioning
confidence: 99%